Impact of Dividend Declarations on the Share Prices: The Case of Dhaka Stock Exchange - Mizan, A. N. K. (Asian Accounting and Auditing Advancement, 2014)
Observing the price movements of stocks is an area of interest for researchers across the world. Possibly no other area of finance has been subject to the empirical investigation during the last four decades relative to stock price movements. The study is an effort to contribute positively to the field. Especially to understand the price movements of stocks listed in the DSE (Dhaka Stock Exchange) as best shares in relation to the dividend declarations of the selected companies. Usually, the dividend declarations are assumed as a positive signal to the market because they signify better earnings for the company. For understanding the price behavior of the shares a standard event study methodology has been adopted to analyze the 20 companies of the DSE-20 index. The findings indicate that the prices are highly influenced by the enormous expectations of the investors and there is a very high possibility to gain abnormal returns by using the publicly available information.